How do dinosaurs learn their colors? - Yolen, Jane; Teague, Mark (New York : Blue Sky Press, 2006)
Illustrations and rhyming text show dinosaurs learning the names of all the colors of the rainbow.
On board pages.
Cover title.
Keywords: Color -- Fiction; Dinosaurs -- Fiction; Stories in rhyme